Dwarf AGNs from Optical Variability for the Origins of Seeds (DAVOS): Insights from the dark energy survey deep fields - Burke, Colin J; Liu, Xin; Shen, Yue; Phadke, Kedar A; Yang, Qian; Hartley, Will G; Harrison, Ian; Palmese, Antonella; Guo, Hengxiao; Zhang, Kaiwen; Kron, Richard; Turner, David J; et al. (Oxford University Press (OUP), 2022)
We present a sample of 706, z < 1.5 active galactic nuclei (AGNs) selected from optical photometric variability in three of the Dark Energy Survey (DES) deep fields (E2, C3, and X3) over an area of 4.64 deg2. We construct light curves using difference imaging aperture photometry for resolved sources and non-difference imaging PSF photometry for unresolved sources, respectively, and characterize the variability significance. Our DES light curves have a mean cadence of 7 d, a 6-yr baseline, and a single-epoch imaging depth of up to g ∼24.5. Using spectral energy distribution (SED) fitting, we find 26 out of total 706 variable galaxies are consistent with dwarf galaxies with a reliable stellar mass estimate (M∗< 109.5, M· median photometric redshift of 0.9). We were able to constrain rapid characteristic variability time-scales (∼weeks) using the DES light curves in 15 dwarf AGN candidates (a subset of our variable AGN candidates) at a median photometric redshift of 0.4. This rapid variability is consistent with their low black hole (BH) masses. We confirm the low-mass AGN nature of one source with a high S/N optical spectrum. We publish our catalogue, optical light curves, and supplementary data, such as X-ray properties and optical spectra, when available. We measure a variable AGN fraction versus stellar mass and compare to results from a forward model. This work demonstrates the feasibility of optical variability to identify AGNs with lower BH masses in deep fields, which may be more 'pristine' analogues of supermassive BH seeds.
Keywords: black hole physics; galaxies: Active; galaxies: dwarf